Access to paediatric oncology centres in Switzerland: Disparities across rural–urban and Swiss‐foreigners cohorts. (9th August 2022) - Rauch, Sebastian; Rakic, Milenko; Hengartner, Heinz; Elger, Bernice; Rost, Michael
Abstract: Objective: In face of disparities in access to cancer care, it has been proposed to measure accessibility and to explore policy strategies for mitigating inequality of access. We aimed to determine the accessibility of Swiss paediatric oncology centres. Methods: We employed spatial accessibility analysis, calculating driving time to nearest facility. Four data types were used: disaggregated population data, administrative data, street network data and addresses of centres. Besides analysing general accessibility, we compared access of urban versus rural areas and of Swiss citizens versus foreign residents and evaluated designating a new centre to improve accessibility. Results: Overall, 97.4% could reach the nearest centre within 120 min (95.0% < 90 min, 86.5% < 60 min, 48.5% < 30 min). Accessibility could most effectively be improved by a new centre in Sion (city in the southwest of Switzerland). Access in urban areas was better than in rural areas. In urban areas, access of European Union/European Free Trade Association (EU/EFTA) and non‐European residents was better than access of Swiss citizens and residents from non‐EU European countries. Conclusion: Access is satisfactory. However, our study presents high‐resolution insights which could serve as points of leverage for policymakers to mitigate inequalities by designating a new centre and to evaluate potential benefits of centralisation.